Design of Roadsite Unit (RSU) Based On ESP32 for Vehicle to Infrastructure (V2I) Communication System: Design of Roadsite Unit (RSU) Based On ESP32 for Vehicle to Infrastructure (V2I) Communication System - Bakti Viyata Sundawa; Afritha Amelia; Ida Susanti (Institute of Computer Science (IOCS), 2019)
Number of vehicle users are increasing in Polmed now. The increasing is very huge if we compare limited campus land. As result of these conditions, disturbing convenience and productivity. Solution to overcome of this condition is implementing of communication system on vehicle user to reach information about outdoor condition. This system is known as Vehicle to Infrastructure (V2I) communication system. The infrastructure is here as roads and parking lots. V2I devices consists of OBU (Onboard Unit), RSU (Roadside Unit) and communication among them. There are some disturbances on the outdoor wireless network such as propagation, interferences, and coverage area. That’s why in this study, how to design RSU device as Transceiver. RSU is made by Microcontroller ESP32. The stages of designing is consist of 3 stages, namely hardware and communication design, localhost-based information design and data measurement and monitoring. According to measurement, height positions of RSU is 3 m, the longest distance RSU toward OBU is 90 m, obtained power is -91 dBm. This value is still in device sensitivity of Microcontroller ESP32.